2020
DOI: 10.9734/cjast/2020/v39i4831276
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Training Systems on Cucumber (Cucumis sativus L.) cv. Malini Grown under Protected Conditions

Abstract: The present investigation was conducted during 2016 and 2017 in Greenhouse at Vegetable Research Block, College of Horticulture Mojerla, Sri Konda Laxman Telangana State Horticultural University, Mulugu to clear the delusion among the farmers on the effect of different training systems on cucumber grown under protected conditions. The experiment comprised of a total of twelve treatments; Three training systems viz., T1 (Single Head Training System), T2 (Umbrella Training System), and T3 (Low Middle Training Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These branches are then carefully trained to grow downward, with a fruit allocated to each axil, promoting balanced fruiting and efficient space utilization. Shivaraj et al [6] revealed that Single head training system reported highest vine length, wider leaf area, more number of fruits per vine, highest fruit yield per vine, yield per plot, yield per hectare, marketable yield and lowest deformed fruits. Therefore, it is recommended that Single Head Training System can be followed in cucumber under protected conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These branches are then carefully trained to grow downward, with a fruit allocated to each axil, promoting balanced fruiting and efficient space utilization. Shivaraj et al [6] revealed that Single head training system reported highest vine length, wider leaf area, more number of fruits per vine, highest fruit yield per vine, yield per plot, yield per hectare, marketable yield and lowest deformed fruits. Therefore, it is recommended that Single Head Training System can be followed in cucumber under protected conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Increased flowering intensity resulting from stress indicates that flower differentiation occurs during moisture stress, and generative buds remain undeveloped until water is supplied. Moisture stress, followed by relief, effectively triggers vegetative growth [21,30,33,50]. Extended periods of stress, caused by factors like extreme temperature and humidity, can delay flowering [83].…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of distinct training systems enhances a plant's capacity to access the requisite sunlight, thereby creating a conducive micro-environment and mitigating the risks of fungal and insect-related issues. The manipulation of canopy structure through suitable spatial arrangements, achieved through strategic training, emerges as a pivotal management approach in achieving desirable and marketable yields in greenhouse cultivation of cucumbers [5,6]. In the Indian context, there exists a scarcity of comprehensive investigations concerning cucumber production within protected environments.…”
Section: Introductionmentioning
confidence: 99%